Further evidence on environmental impacts of carbon monoxide from portable power generator on indoor air quality. Issue 1 (1st January 2020) - Adefeso, Ismail Babatunde; Sonibare, Jacob Ademola; Isa, Yusuf Markafi
Abstract: The indoor air quality (IAQ) is paramount to the existence of humans considering the amount of time spent indoors. The indoor pollutant levels may be 100 times the levels outdoors. The indoor pollutants need to be considered to enhance better IAQ. This study determined the emission factors of carbon monoxide (CO) emitted from a standby electricity generator (SEG). It evaluated the impacts of CO concentrations on indoor air quality and identified appropriate ways to mitigate the CO concentrations. The indoor CO concentration was determined by simulating a number of scenarios of SEG operated outdoor using a Simulation Tool Kit for Indoor Air Quality and Inhalation Exposure (IAQX) model. Hourly measurements of mean CO concentrations in the ambient environment and wind speed were conducted for four weeks in four field locations. The emission rate of CO from the standby electricity generator was measured. The CO concentration from SEG was 2.4289 × 10 4 mg/m 3, a very high CO concentration. The CO emission factors were obtained as 2.2366 × 10 3 kg/m 3 of fuel consumed and 9.5411 × 10 6 kg/hr of activity. High CO concentrations were obtained in microenvironments from the scenarios 1.28 × 10 4 mg/m 3, 4.78 × 10 3 mg/m 3, 4.79 × 10 4 mg/m 3 and 9.58 × 10 4 mg/m 3 . The results showed that a high air exchange rate allowed CO concentrations to decay fast while low air exchange rates created an accumulation of CO concentrations indoor.